2015
DOI: 10.1007/s10571-015-0305-4
|View full text |Cite
|
Sign up to set email alerts
|

Propensity of Withania somnifera to Attenuate Behavioural, Biochemical, and Histological Alterations in Experimental Model of Stroke

Abstract: The present study was designed to evaluate the beneficial effects of Withania somnifera (WS) pre-supplementation on middle cerebral artery occlusion (MCAO) model of ischemic stroke. Ischemic stroke was induced in the rats by inserting intraluminal suture for 90 min, followed by reperfusion injury for 24 h. The animals were assessed for locomotor functions (by neurological deficit scores, narrow beam walk and rotarod test), cognitive and anxiety-like behavioural functions (by morris water maze and elevated plus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Ashwaganda has beneficial effects on diseases of cardiovascular nature (Ravindran et al, 2015a), obesity, diabetes, infection, cancer (Choi and Kim, 2015, Khazal et al, 2014, Rai et al, 2016), arthritis (Gupta and Singh, 2014, Khan et al, 2015) and gastric inflammation (Kim et al, 2016). The major constituent in Ashwaganda, identified as Withaferin A, itself is an inhibitor of HMG-CoA, angiotensinogen-converting enzyme, (Ravindran et al, 2015b) can lower total cholesterol, triglycerides, higher HDL/LDL ratios (Shukla et al, 2014) and reduce severity or incidence of myocardial infarction, (Khalil et al, 2015) stroke (Ahmad et al, 2015, Raghavan and Shah, 2015, Sood et al, 2015) and hypertension. (Kaur et al, 2015) As far as glial cells, little has been investigated, but it has been reported that Withaferin A has potential in treatment of glioblastoma multiforme (Chang et al, 2016) with possible future therapies to target brain tumors (Kataria et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Ashwaganda has beneficial effects on diseases of cardiovascular nature (Ravindran et al, 2015a), obesity, diabetes, infection, cancer (Choi and Kim, 2015, Khazal et al, 2014, Rai et al, 2016), arthritis (Gupta and Singh, 2014, Khan et al, 2015) and gastric inflammation (Kim et al, 2016). The major constituent in Ashwaganda, identified as Withaferin A, itself is an inhibitor of HMG-CoA, angiotensinogen-converting enzyme, (Ravindran et al, 2015b) can lower total cholesterol, triglycerides, higher HDL/LDL ratios (Shukla et al, 2014) and reduce severity or incidence of myocardial infarction, (Khalil et al, 2015) stroke (Ahmad et al, 2015, Raghavan and Shah, 2015, Sood et al, 2015) and hypertension. (Kaur et al, 2015) As far as glial cells, little has been investigated, but it has been reported that Withaferin A has potential in treatment of glioblastoma multiforme (Chang et al, 2016) with possible future therapies to target brain tumors (Kataria et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The number of records in PubMed for the key word “ Withania somnifera ” has considerably increased from 43 between 1990 and 2000 [ 9 , 10 ], to 275 in the period relative to 2000 – 2010 [ 11 , 12 ]. In addition, the 566 studies collected in the period relative to 2010 – 2017 [ 13 , 14 ] (up to the time of preparation of the manuscript) represent more than half of the total 915 citations found with this key word search.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, Withania somnifera (WS) which is a similar species as that of Withania coagulans (WC) had been tested for the motor coordination using Rota rod apparatus in middle cerebral artery occluded (MCAO) rodents. It was found that WS had significantly (p<0.05) "increased" the performance of MCAO rodents treated with WS root extract on Rota rod apparatus [17]. Hence it can be concluded that the different withanoloides in both the species might be responsible for this activity.…”
Section: Discussionmentioning
confidence: 91%